BUDIDAYA AYAM KUB BERBASIS PAKAN FERMENTASI DI KECAMATAN TERNATE SELATAN - Sri Utami; Emy Saelan; Muhammad Aldi (Bajang Institute, 2022)
Cultivation of chicken Kampung Unggul Balitnak (KUB) is carried out with the aim of meeting the community’s need free native chicken meat. Through the Partnership Community Program (PKM) training activities for KUB chicken cultivation based and fermented feed were carried out, which in this activity began with the Socialitization of KUB Chicken Cultivation covering maintenance, feeding and disease prevention. The Cultivation system that is applied to the partner's livestock group in this PKM activity is carried out intensively, so that its maintenance can be directly controlled by the breeder. Besides training in the manufacture of fermented feed, farmers can provide quality feed and meet nutrient standards for growth and production. The result of PKM is that the Partner Livestock Group can develop intensive KUB chicken cultivation with feed produced or formulated by farmers, so as to reduce the use of factory feed.